Peran Motivasi Belajar Pada Hubungan Kemandirian Belajar Dan Kepercayaan Diri Terhadap Kemampuan Berfikir Kritis - Fidya Serlinawati; Novi Trisnawati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Responding to the problem of low critical thinking skills at SMK Negeri 4 Surabaya, this research aims to determine the direct influence of learning independence and self-confidence on critical thinking skills, the indirect effect of learning independence and learning self-confidence on critical thinking skills with learning motivation as an intervening variable. This type of research is explanatory research and uses saturated sampling techniques. The population of this research includes all students in classes X and XI concentrating on Office Management skills at SMK Negeri 4 Surabaya with a total sample of 175 students. The questionnaire data collection technique was analyzed using path analysis with the help of SmartPLS software. The results of the research show that independent learning has a direct positive and significant effect on critical thinking skills. Self-confidence also has a direct positive and significant influence on critical thinking abilities.